COMET phase-I technical design report - Abramishvili,R; Adamov,G; Akhmetshin,RR; Allin,A; Angelique,JC; Anishchik,V; Aoki,M; Aznabayev,D; Bagaturia,I; Ban,G; Ban,Y; Bauer,D; et al. (Progress of Theoretical and Experimental Physics, 2020)
The Technical Design for the COMET Phase-I experiment is presented in this paper. COMET is an experiment at J-PARC, Japan, which will search for neutrinoless conversion of muons into electrons in the field of an aluminum nucleus (μ–e conversion, μ−N→e−N); a lepton flavor-violating process. The experimental sensitivity goal for this process in the Phase-I experiment is 3.1×10−15, or 90% upper limit of a branching ratio of 7×10−15, which is a factor of 100 improvement over the existing limit. The expected number of background events is 0.032. To achieve the target sensitivity and background level, the 3.2 kW 8 GeV proton beam from J-PARC will be used. Two types of detectors, CyDet and StrECAL, will be used for detecting the μ–e conversion events, and for measuring the beam-related background events in view of the Phase-II experiment, respectively. Results from simulation on signal and background estimations are also described.